2007
DOI: 10.1063/1.2772500
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural properties of Si nanocrystals produced by Si hot implantation

Abstract: It was already demonstrated that Si hot implantation followed by high-temperature annealing induces the formation of Si nanocrystals ͑Si NCs͒ which when excited in a linear excitation regime present two photoluminescence ͑PL͒ bands ͑at 780 and 1000 nm͒. We have undertaken the present work in order to investigate three features: First, to determine the origin of each band. With this aim we have changed the implantation fluence and the high-temperature annealing time. Second, to investigate the influence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
0
15
2
Order By: Relevance
“…Therefore, the PL of these structures relies entirely on the quantum confinement effect of Si QDs. This conclusion is not general and might be invalid for the structures realized using different deposition techniques [20][21][22]. The discrepancy between data presented here and theoretical calculations, shown in Fig.…”
Section: Investigation Of Forming Gas Hydrogenation On Photoluminescecontrasting
confidence: 75%
See 2 more Smart Citations
“…Therefore, the PL of these structures relies entirely on the quantum confinement effect of Si QDs. This conclusion is not general and might be invalid for the structures realized using different deposition techniques [20][21][22]. The discrepancy between data presented here and theoretical calculations, shown in Fig.…”
Section: Investigation Of Forming Gas Hydrogenation On Photoluminescecontrasting
confidence: 75%
“…These specimens should have a higher defect density compared to the annealed specimens. Other authors have observed high energy PL signals on as-deposited samples realized by ion implantation of Si in SiO 2 [21,22]. In this case PL could be attributed to matrix defects caused by ion-implantation damage.…”
Section: Photoluminescence Of Single Layers Si Qds In Siomentioning
confidence: 92%
See 1 more Smart Citation
“…The most important property of these nanocrystals is the intense photoluminescence in the visible and the red/near-infrared ranges of the optical spectrum [2,3]. This is why Si nanocrystals are potential candidates for Si-based optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nanocrystals generated in a SiO 2 matrix have attracted considerable interest due to their excellent optical and electronic properties [1][2]. The most important property of these nanocrystals is the intense photoluminescence in the visible and the red/near-infrared ranges of the optical spectrum [2,3].…”
Section: Introductionmentioning
confidence: 99%